Bending of Layer-by-Layer Films Driven by an External Magnetic Field - Miyazaki, Celina M.; Riul, Antonio; Dos Santos, David S.; Ferreira, Mariselma; Constantino, Carlos J. L. [UNESP]; Pereira-da-Silva, Marcelo A.; Paupitz, Ricardo [UNESP]; Galvao, Douglas S.; Oliveira, Osvaldo N. (Mdpi Ag, 2013)
We report on optimized architectures containing layer-by-layer (LbL) films of natural rubber latex (NRL), carboxymethyl-chitosan (CMC) and magnetite (Fe3O4) nanoparticles (MNPs) deposited on flexible substrates, which could be easily bent by an external magnetic field. The mechanical response depended on the number of deposited layers and was explained semi-quantitatively with a fully atomistic model, where the LbL film was represented as superposing layers of hexagonal graphene-like atomic arrangements deposited on a stiffer substrate. The bending with no direct current or voltage being applied to a supramolecular structure containing biocompatible and antimicrobial materials represents a proof-of-principle experiment that is promising for tissue engineering applications in biomedicine.
Keywords: magnetic nanoparticles; natural rubber latex; carboxymethyl-chitosan; layer-by-layer assembly; molecular dynamics